Mechanisms of resistance in maize grain to the maize weevil and the larger grain borer - Arnason, J.T.=700 1 Conilh de Beyáac, B.; Philogene, B.J.R.; Bergvinson, D.; Serratos, J.A.; Mihm, J.A.
Sumario (En)
Ilus.; 11 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; TECNICAS ANALITICAS; SITOPHILUS ZEAMAIS; GENOTIPOS